2015
DOI: 10.1249/mss.0000000000000687
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High-Intensity Intermittent Exercise Training on Appetite Regulation

Abstract: HIIT seems to benefit appetite regulation in overweight men. The mechanisms for this remain to be elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(91 citation statements)
references
References 30 publications
(34 reference statements)
6
81
2
2
Order By: Relevance
“…The intensity of effort in most SIT protocols (n=13) was prescribed by ‘all-out’ efforts,24 60–62 69 71 72 74 83 84 88 89 91 percentage of i true0V˙ O 2 peak,80 percentage of maximal power output75 and percentage of anaerobic power 79…”
Section: Resultsmentioning
confidence: 99%
“…The intensity of effort in most SIT protocols (n=13) was prescribed by ‘all-out’ efforts,24 60–62 69 71 72 74 83 84 88 89 91 percentage of i true0V˙ O 2 peak,80 percentage of maximal power output75 and percentage of anaerobic power 79…”
Section: Resultsmentioning
confidence: 99%
“…Another possible confounding factor might have been the compensatory eating responses to exercise protocols that were not accounted for during the intervention, with possible implications on glycaemic control. There is a lack of consensus in the literature regarding the impact of HIIT on appetite regulation, with some studies suggesting a beneficial impact, while others showed no impact …”
Section: Discussionmentioning
confidence: 99%
“…5,13,16,27,28 Another possible confounding factor might have been the compensatory eating responses to exercise protocols that were not accounted for during the intervention, with possible implications on glycaemic control. There is a lack of consensus in the literature regarding the impact of HIIT on appetite regulation, with some studies suggesting a beneficial impact, 30 while others showed no impact. 31 When addressing the issue of which type of exercise led to greater improvements in glycaemic control (HIIT vs MCT), there is no experimental evidence to support that HIIT led to superior results in individuals with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Sim and colleagues 55 examined the impact of a HIFT-based program on appetite regulation in 30 overweight, inactive men. Participants were randomized to either 12 weeks of high intensity intermittent exercise consistent with HIFT or moderate intensity continuous training (MICT).…”
Section: Health Body Composition and Fitness Benefits Of Hift Trainingmentioning
confidence: 99%